TREATMENT OF REAL PARACETAMOL WASTEWATER BY FENTON PROCESS - Dalgic, Gamze; Turkdogan, F. Ilter; Yetilmezsoy, Kaan; Kocak, Emel (ASSOC CHEMICAL ENG, 2017)
The study investigated the pretreatment of real paracetamol (PCT) wastewater of a pharmaceutical industry by Fenton process. At the best experimental conditions (COD/H2O2 = 1/1, Fe+2/H2O2 = 1/70, settling method:centrifuging, pH 6 at settling step), 92.7, 92.7, 95.5, 99.1, 99.9 and 99.4% of chemical oxygen demand (COD), total organic carbon (TOC), 5-day biological oxygen demand (BOD5), PCT, para-amino phenol (PAP) and aniline were removed, respectively. Changes in the concentrations of these parameters were also investigated for both oxidation and settling steps of Fenton process. It was found that COD and TOC were removed at the settling step (precipitation) whereas PCT, PAP and aniline were removed at the oxidation step. Mass balance calculations were also studied to show the mass distributions of COD in different phases (gas + foam, effluent and sludge). Fenton process was found as an effective method for the pretreatment of real PCT wastewater for discharging in a determined collective treatment plant.
Keywords: chemical oxygen demand; Fenton process; mass balance; real paracetamol wastewater; total organic carbon; PERSONAL CARE PRODUCTS; OXIDATION PROCESSES; DEGRADATION; PHARMACEUTICALS; REMOVAL; ANTIBIOTICS; EFFLUENT; SYSTEMS; IMPROVE; TIO2; Chemistry; Engineering